Preparação e caracterização de sistemas emulsionados lipidicos contendo praziquantel - Araujo, Margarete Moreno de (2013)
Praziquantel (PRZ) is the main drug used for treatment of schistosomiasis in Brazil. It is administered by oral rout as tablets. However, has low aqueous solubility which limits this therapeutic success dosage form and availability of liquid forms. The emulsion systems have great potential and represent an interesting strategy to increase the solubility of drugs. The aim of study was the development and characterization of lipid-emulsified liquid systems of the type oil in water (O / W), the base of soybean oil as the internal phase stabilized by surfactants pair Tween® 80 and Span® 80, for improving the phase biopharmaceutical of PRZ. After selecting the best value of Hydrophilic-Lipophilic Balance (HLB = 11), the parameters of the preparation of the formulations were optimized emulsification technique. The emulsions were successfully obtained; the liquid forms provided exhibited Newtonian behavior and an increase in solubility of PRZ higher than 20 times. The accelerated stability study demonstrated the stability of the emulsions and the effect of cosurfactants investigated. The study of the dynamics of interaction between components in the diagram showed pseudoternary phase regions to obtain O/W emulsions, whereas the study of the interaction of the components and their effect on system structure and the efficiency of incorporation of the drug led to systems with an amount of soluble drug even higher (about 1.5%), which demonstrates the potential of this new input mainly for the treatment of schistosomiasis, which resulted in the filing of patent BR 10 2013 0004 55 3